PERTIMBANGAN AGAMA CALON KEPALA DAERAH DAN ANGGOTA LEGISLATIF BAGI PEMILIH MUDA - Syarifudin, Ahmad (Moderatio: Jurnal Moderasi Beragama, 2023)
Religion-based identity politics is often carried out in the Pilkada and General Elections to accumulate support by the people. This study focuses on exploring religion considerations in the election of regional heads and legislative members for young voters by proposing two problem formulations, namely: 1) what are the views of young voters on religion and the state, especially on aspects of the implementation of elections and leadership in both the executive and legislative branches?; 2) what are the views of young voters on candidates for legislative members and Muslim or non-Muslim regional heads in the 2024 Simultaneous General Election and Regional Head Elections? Using qualitative methods with primary and secondary data sources which were then analyzed descriptively, concluded that: first, young voters view religion as a very important and main thing in determining candidates for regional heads and candidates for legislative members based on the relationship between state and religion in Indonesia which very strong, regardless of religion. Second, the criteria for Muslim or non-Muslim leaders for most young voters are not the first and foremost, because the important factor lies in the candidate's ability to carry out their duties. However, there are still more than 26 percent of respondents who will continue to prioritize Muslim leaders for reasons of Islamic doctrine and history in the past.